Verocytotoxin-producing Escherichia coli, Japan, 1999–2004 - Sakuma, Mio (Centers for Disease Control and Prevention, 2006)
In 1999, an infectious disease prevention law was enacted in Japan that affected the nationwide infectious surveillance system. A total of 19,304 laboratory-confirmed verocytotoxin-producing Escherichia coli cases were reported through 2004. The annual incidence was 2.74/100,000 population; its fluctuation over time and space was associated with climate, socioeconomic, and population factors.